Effect of Nanoparticles Concentration on Rheological Behavior of Silica-Fe3O4 Hybrid Nanofluid - Aznan, Muhammad Hakeem (2018)
Nanoparticles has become the center of attraction amongst researchers lately particularly because of its unique characteristics. In the oil and gas industry, recently, nanofluid has shown contribution in the oil recovery process. The nanoparticles is able to alter the condition in the oil well, thus causing more oil to be able to recover. In the tertiary recovery, to achieve oil recovery, a fluid used need to be able to have better viscosity compared to brine, to alter the interfacial tension between oil and reservoir rocks and change the wettability of the rocks. However, one nanoparticles might show different characteristics than the others. That is why hybrid nanoparticles are chosen so that the nanofluid will have all of the individual nanoparticles properties. From there, enhance nanofluid can be created. During the preparation process, both the silica and magnetite nanoparticles is dispersed in brine solution. Different ratio is used to see how it will change the properties. This research focuses on the rheological performance of Silica-Fe3O4 nanofluid with difference weight percentage towards enhance oil recovery. Nanofluid with the best viscosity, lowest interfacial tension, and has the ability to alter the oil wettability is determined to be Silica-Fe3O4 nanofluid with 50-50 wt%.